Assisting college students with athletic disengagement. - Van Lone, Jeffrey S.; Siembor, Michael; Mistler, Brian J; Mapstone, David J (Journal of College Student Psychotherapy, 2017)
This article examines college student disengagement from sports, presents a multidimensional concept of athletic identity, and introduces a new measure intended to assist college counselors in their work with disengaged athletes. The Multidimensional Athletic Identity and Engagement Scale (MAIES) is introduced (Cronbach alpha.98, with subscale alphas between.78 and.96), and the results of exploratory and confirmatory factor analyses and convergent and divergent validity with 250 college student participants are presented. Using case examples, the authors discuss how counselors may use the MAIES in their work with students. Limitations of the study and suggestions for future research are discussed. © 2017 Taylor & Francis.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/068-482-146-748-575 tex.type: [object Object]
Keywords: Cronbach alpha coefficient; athlete; athletic disengagement; athletic identity; college student; college students; counseling; counselor; dept.counseling; factor analysis; human; identity; major clinical study; sport; validity